Islamic Religious Education Teachers' Strategies In Instilling Students' Religious Character In Mis Al-Hikmah - M. Alfarizi Tobing; Kamil (International Journal of Society and Law, 2025)
This study aims to analyze the strategies of Islamic religious education teachers in instilling students' religious character in MIS AlHikmah. Through the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach, this study identifies factors that affect the success or challenges in the process of religious education. The results of the analysis show that the main strength lies in the in-depth competence of teachers, varied teaching methods, and support from the curriculum and MIS AlHikmah. On the other hand, there are weaknesses such as lack of adequate training for teachers and limited teaching time. The study also found that opportunities such as the use of educational technology and religion-based extracurricular activities can strengthen students' religious character. However, there is a threat in the form of social media and global cultural influences that can reduce the practice of religious teachings. Based on the results of the analysis, this study suggests a number of policies, including increasing teacher training, increasing religious learning time, and developing religion-based extracurricular activities. It is hoped that the implementation of this policy can increase the effectiveness of Islamic religious education in shaping the religious character of students at MIS AlHikmah.